Cost-effectiveness of empagliflozin for the treatment of heart failure with reduced ejection fraction in China - Sang, Haiqiang; Wan, Yiming; Ma, Zhenzhou; Zhang, Shengye; Zhao, Qiuping (Frontiers in Cardiovascular Medicine, 2022)
Aim: To determine the pharmacoeconomics of empagliflozin for the treatment of heart failure with reduced ejection fraction in China and to provide evidence-based reference for clinical rational drug selection and medical decision-making. Research Design and Methods: We used the Markov model to evaluate the cost-effectiveness of empagliflozin for the treatment of heart failure with reduced ejection fraction. We evaluated the cost-effectiveness of the standard treatment in addition to empagliflozin (empagliflozin group) versus the cost-effectiveness of the standard treatment alone (standard treatment group). Results: We found that each additional quality-adjusted life year in the empagliflozin group costed $3,842.20 more, which was less than China's gross domestic product (GDP) per capita in 2021 ($11,981). The steady-state mortality in the two groups was the key factor affecting the incremental cost-effectiveness ratio. Probabilistic sensitivity analysis revealed that when the willingness-to-pay threshold was one time the GDP per capita in 2021 ($11,981) and three times the GDP per capita in 2021 ($35,943), the probability of the empagliflozin group being cost-effective was 85.8% and 91.6%, respectively. Conclusions: Compared with the standard treatment alone, the addition of empagliflozin to the standard treatment was more cost-effective for the treatment of heart failure with reduced ejection fraction in China.